The Environmental Education and her role to protect an Environment (Journal of the College of Education for Women, 2019)
Environmental education is considered as process of getting Humans in communication with this environment and all its various resources. such process requires acquiring knowledge about the environment that com help humans understand their correlative relations with the environmental elements on one hand and among the environmental elements themselves on the other . Besides, such a process requires developing human skills that help them participate in developing environmental circumstances. Therefore environmental education is responsible for perspective and cultural development that governs human behavior. Regarding their environment and stimulating tendencies and interests towards the environment , let alone helping humans acquire the care for environmental maintenance and investing environmental resources .they , future of life is related to human position and care regarding .So we can say that environmental education is aimed at enabling the human from the realization that an influential object in the environmental entity and unaffected by it, and it's an integral part of this entity, depending on the quality of his just how good exploitation of the environment and conservation.It is here environmental education is becoming the medium used in the preparation of generations to deal with the normal adjustment or collectively but to exceed its concept that has become a means Petkevh with the natural physical environment through which can maintain its existence as a member of the community in which he lives.